A constructive role for social science in the development of automated vehicles. (July 2020) - Cohen, Tom; Stilgoe, Jack; Stares, Sally; Akyelken, Nihan; Cavoli, Clemence; Day, Jennie; Dickinson, Janet; Fors, Vaike; Hopkins, Debbie; Lyons, Glenn; Marres, Noortje; Newman, Jonathan; et al.
Abstract: Automated vehicles (AVs) have the potential to cause profound shifts across a wide range of areas of human life, including economic structures, land use, lifestyles and personal well-being. Most current social science on AVs is narrowly framed. Research on public attitudes has focused on whether people are likely to accept and use AVs. We contend that failing to anticipate a wider range of profound social implications may have serious negative consequences, and that social scientists from a range of disciplinary perspectives can provide invaluable insights. Our conclusions are the product of a workshop in London held in 2018 to discuss the place of social science research in relation to the development of AVs. This paper summarises a core selection of our concerns, interests, theoretical and substantive points of reference and aspirations for a constructive role in this field of research and development. Highlights: Automated vehicles are likely to have profound and far-reaching ramifications for society The majority of research to date centres on impacts within the transport system The role of social science in this research has been narrowly framed A fuller role for social science would explore a wider range of social possibilities and enable better-informed policy